Chaotic genetic structure and past demographic expansion of the invasive gastropod Tritia neritea in its native range, the Mediterranean Sea - Emilie Boissin (Nature Portfolio, 2020)
Abstract To better predict population evolution of invasive species in introduced areas it is critical to identify and understand the mechanisms driving genetic diversity and structure in their native range. Here, we combined analyses of the mitochondrial COI gene and 11 microsatellite markers to investigate both past demographic history and contemporaneous genetic structure in the native area of the gastropod Tritia neritea, using Bayesian skyline plots (BSP), multivariate analyses and Bayesian clustering. The BSP framework revealed population expansions, dated after the last glacial maximum. The haplotype network revealed a strong geographic clustering. Multivariate analyses and Bayesian clustering highlighted the strong genetic structure at all scales, between the Black Sea and the Adriatic Sea, but also within basins. Within basins, a random pattern of genetic patchiness was observed, suggesting a superimposition of processes involving natural biological effects (no larval phase and thus limited larval dispersal) and putative anthropogenic transport of specimens. Contrary to the introduced area, no isolation-by-distance patterns were recovered in the Mediterranean or the Black Seas, highlighting different mechanisms at play on both native and introduced areas, triggering unknown consequences for species’ evolutionary trajectories. These results of Tritia neritea populations on its native range highlight a mixture of ancient and recent processes, with the effects of paleoclimates and life history traits likely tangled with the effects of human-mediated dispersal.